METODE PELAKSANAAN KONTRUKSI PEKERJAAN GROUTING PADA BAGIAN SADDLEDAM BENDUNGAN CIPANAS - Diki Subagdja; LIA LAILLA NURJAMILA (Universitas Majalengka, 2021)
Cipanas Dam Construction Project, in the village of Pasir Cadasngampar, Cibuluh Village, Ujung Jaya District, Sumedang-Indramayu Regency, West Java Province. The Grouting Work Implementation Method is in the saddle dam section which consists of Trial Work, Drilling / Drilling, WPT, Grouting, and Check Hole Work. Drilling is carried out by split spacing (chessboard) on Curtain Grouting (curtain grouting) work carried out to a depth of 20 m, with 1 stage having a depth of 5 m, and each point grouting distance of 2 m, using the Down Stage method. The implementation of the Water Pressure Test at the Cipanas Dam Construction Project is carried out by means of a single test and multi-test. Grouting work is aimed at making the soil existing in the foundation of the fascial dam, the main purpose of grouting is to reduce the intensity of the filter flow / leakage in the saddle dam